2022
DOI: 10.1024/0301-1526/a001005
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey study on the nutrition patterns of patients with peripheral artery disease

Abstract: Summary: Background: Even though nutrition was demonstrated to have an impact on chronic atherosclerotic disease, there is a paucity of corresponding recommendations for patients with peripheral artery disease (PAD). A Mediterranean Diet based on daily intake of fruits and vegetables with high fibre, vegetable oil, and unsalted nuts including fish several times a week may have protective effects. This cross-sectional survey aimed to determine nutritional patterns amongst inpatients with PAD. Methods: All inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Due to the complexity of earlier PNIs in clinical practice, Onodera’s calculation method, based on peripheral blood lymphocyte counts and serum ALB levels, became simpler 19. Several studies have demonstrated a clear association between PNI and atherosclerotic disease 17 20 21. However, the majority of these studies have been performed in the general population or in those at high risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexity of earlier PNIs in clinical practice, Onodera’s calculation method, based on peripheral blood lymphocyte counts and serum ALB levels, became simpler 19. Several studies have demonstrated a clear association between PNI and atherosclerotic disease 17 20 21. However, the majority of these studies have been performed in the general population or in those at high risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, providing advice about nutrition adaptation being efficacious on lipidlowering should be a standard approach, however, a minority of patients are presented with this preventive strategy [24].…”
Section: Treatment Recommendation For Dietary Adaptationsmentioning
confidence: 99%
“…Against this background, we hypothesized that the increased inflammatory potential of dietary intake might also be related to the prevalence of PAD. At present, the role of several common dietary indexes and some food in PAD has been investigated in some studies [24,25]. In 2014, Naqvi et al reported that the prevalence of PAD was negatively associated with the intake of fiber, folate, and vitamins A, B6, C, and E after adjusting for age, sex, hypertension, diabetes, and smoking [26].…”
Section: Introductionmentioning
confidence: 99%